KUALITAS SUBJEKTIF SEKOLAH RAMAH ANAK USIA DINI DI JAWA BARAT - Susanti, Indah Susanti (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2023)
Abstract: School facilities and infrastructure, not only have to meet standards from a physical perspective, but also have to be early childhood friendly schools. This study aims to describe the architectural condition of early childhood schools in West Java based on the fulfillment of the school's physical standard requirements. This study uses a descriptive quantitative approach. Quantitative methods are used for the collection and analysis of quantitative data regarding the architectural condition of PAUD schools. Respondents, a total of 167 people who filled out a Google form questionnaire that was distributed online, were teachers, school principals, deputy principals, and school owners/heads of kindergarten/PAUD foundations. Based on the description of the research results, it can be concluded that in general the respondents' subjective perceptions of their schools indicate that most PAUD schools are architecturally child-friendly. On average, more than 70 percent of respondents, from the group of owners, principals/deputy principals, and teachers, as well as based on regional origin groups, said that their schools were in the category of friendly and very child-friendly.Keywords: Child Friendly Schools, PAUD, Architectural..Abstrak: Sarana dan prasarana sekolah, bukan saja harus memenuhi standar dari segi fisik, tapi juga harus menjadi sekolah ramah anak usia dini. Penelitian ini bertujuan untuk mendeskripsikan kondisi arsitektural sekolah anak usia dini di Jawa Barat berdasarkan pemenuhan persyaratan standar fisik sekolah. Penelitian ini menggunakan pendekatan kuantitatif deskriptif. Metoda kuantitatif digunakan untuk pengumpulan dan analisis data kuantitatif mengenai kondisi arsitektural sekolah PAUD. Responden sejumlah 167 orang mengisi angket google form yang disebar secara online adalah guru, kepala sekolah, wakil kepala sekolah, dan pemilik sekolah/ketua yayasan TK/PAUD. Berdasarkan deskripsi hasil penelitian dapat disimpulkan bahwa secara umum persepsi subjektif responden tentang sekolahnya, menunjukkan bahwa sebagian besar sekolah PAUD secara arsitektural termasuk ramah anak. Rata-rata responden, baik dari kelompok pemilik, kepala sekolah/wakil kepala sekolah, dan guru, maupun berdasarkan kelompok asal daerah, lebih dari 70 persen menyatakan sekolahnya berkategori ramah dan sangat ramah anak.Kata Kunci: Sekolah Ramah Anak, PAUD, Arsitektural.